Penerapan Aplikasi Marketplace Untuk Mendukung Digitalisasi Terhadap Peningkatan Penjualan UMKM Di Grosir Samingan - Pria Mitra Purba (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the implementation of a marketplace application as a means of digitalization to improve sales for micro, small, and medium enterprises (MSMEs), particularly at Grosir SAMINGAN, which still relies on conventional methods such as cash transactions and direct marketing. A qualitative case study approach was used, with data collected through interviews with business owners, direct observation, and literature review. The findings reveal that limited understanding of digital technology and concerns about transaction security are the main obstacles to digital adoption. However, respondents showed strong interest in online shopping, and the store owner expressed willingness to use a marketplace if guided properly. The implemented marketplace system functioned effectively, improved operational efficiency, and expanded market reach for the business. Therefore, the use of a marketplace is considered an effective solution to support digital transformation and enhance the competitiveness of MSMEs in the digital era.